Comparison of acid scarification, stratification and endocarp removal on seed germination of three olive cultivars - Isa Arji; Maryam Rostami Dastjerdi; Mohammad gerdakaneh (علوم و فناوری بذر ایران)
Present study was conducted to evaluate the effects of chemical scarification (Sulphuric acid 97% for 0, 3, 6 and 9 h at 25°C), removal of endocarp and cold stratification (0, 21 and 31 days at 10°C) treatments on percentage and rate of seed germination of olive cultivars (Koroneiki, Zard and Shenghe). A factorial experiment was used based on a completely randomized design with three replications. Results indicated that the chemical scarification treatments and removal endocarp followed by an adequate stratification period can increase seed germination significantly. The best results obtained by removal endocarp treatments. The highest germination percentage of cv. Koroneiki obtained after Cold stratification treatments for 21 days (up to 93%). The best result for cv. Shenghe and cv. Zard observed following Cold stratification treatments for 31 days (85.55% and 84.44 respectively). The highest germination percentage of cv. Koroneiki obtained after 97% sulfuric acid solution treatments for 6 h (49.67%). Treating seeds of this cultivar by 97% sulfuric acid for longer period resulted in damage to embryo and no seedlings emerged after these treatments. The best result for cv. Shenghe observed following 97% sulfuric acid treatment for 9 h (42.34%) cv. Zard observed following 97% sulfuric acid treatment for 6 h (40.23%). The least germination rate and percentage was observed in control treatments. Growth of olive seedlings also increased by scarification, removal endocarp Cold stratification treatments significantly. Results suggested that removal endocarp and chemical mechanical scarification treatments can improve germination percentage and seedling growth of olive cultivars.